Storing grain in the desert - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1986)
Some of the world's poorest regions may be the best natural storehouses for grain, according to a three-year study carried out by Israel's Valcani Institute for Agricultural Research, in cooperation with the Insect Infestation Laboratory in...